مؤشرات القيم المضافة للتعليم المحاسبي الهجين ومتطلبات تحقيقيها في الجامعة الجزائرية: Indicators of the added values of hybrid accounting education and the requirements for its success at the Algerian University - صافو فتيحة (Journal of North African Economies, 2025)
This study aims to highlight the most important indicators of added values for accounting education by using the hybrid education style, which is the style that combines the traditional face-to-face learning system with education via the Internet, with various and advanced technological methods and applications. The effects of the hybrid education style have emerged, especially during and after the global health crisis in many countries. Through the study, the experience of hybrid accounting education in Algeria was evaluated, which relied on the Moodle platform, the pioneer in e-learning. However, the experience faced many challenges and obstacles, mainly represented in the weakness of the technological infrastructure, the lack of experience, practice and objective assessment of student achievement. The study also concluded that achieving the added values of hybrid accounting education at the level of Algerian universities depends on several factors and elements, the most important of which is the availability of material capabilities and the will for change and development on the part of all actors in the educational process.